Developing an integrated conceptual framework of pro-environmental behavior in the workplace through synthesis of the current literature - Faye V. McDonald (Administrative Sciences, 2014)
Recent studies have begun to bridge the gap between general and workplace pro-environmental behavior by adapting specific existing behavioral models to the workplace environment. This conceptual article proposes a different approach by synthesizing the current general and workplace literature to develop a new model of the antecedents to pro-environmental behavior. Guided by this approach, this paper combines the insights of the current general and workplace models to develop an integrated framework of pro-environmental behavior in the workplace. In doing so, an overview of the current general and workplace literatures will be provided as well as their similarities and differences highlighted. The proposed framework will provide further insights into the antecedents of workplace pro-environmental behavior and identify common findings across the different existing workplace models. This theory can be the basis for further research in order to provide a comprehensive picture of the antecedents of pro-environmental behavior in the workplace. Lastly, implications for specific interventions to develop targeted Human Resource Management practices and work towards achieving environmental sustainability will be discussed.
Keywords: 350; pro-environmental behavior; environmental concern; values; attitudes; habit; Theory of Planned Behavior; human resource management; sustainable behavior; organizational behavior; environmental psychology